Salmonella in pet and captive reptiles with reference to some studies in Malaysia and countries worldwide - Abdul Aziz, Saleha; Khor, Kuan Hua; Zakaria, Zunita; Abu, Jalila (Veterinary Association Malaysia, 2015)
Reptiles, which included snakes, chelonians (turtles, tortoises), iguanas and lizards, have been reported as important reservoirs for Salmonella. In Malaysia, reports on Salmonella in reptiles are not many. A search for works in Malaysia on salmonellae in reptiles found 28.0% chelonians, 27.5 - 61.0% snakes, 26.5 – 36.0% lizards and 31.0% house geckos carried Salmonella. The prevalence in some countries worldwide which included the United States of America, Brazil, Japan, Nigeria and few others were shown. The public health risk of the presence of salmonellae particularly in pet reptiles are discussed.